FMR1 premutation: not only important in premature ovarian failure but also in diminished ovarian reserve. (3rd April 2017) - Eslami, Ali; Farahmand, Kamelia; Totonchi, Mehdi; Madani, Tahereh; Asadpour, Ummulbanin; Zari Moradi, Shabnam; Gourabi, Hamid; Mohseni-Meybodi, Anahita
Abstract: It is recognized that FMR1 premutation expansions are associated with premature ovarian failure (POF), but their role in diminished ovarian reserve (DOR) is not clearly established. Moreover, the impact of smaller repeats at the boundary of premutation and normal is less clear. Therefore, we have compared the frequency of these intermediate (45–54 repeats) and premutation (>55) sized FMR1 CGG repeats among a patients group including 188 DOR and 173 POF women and 200 controls. FSH and LH concentrations were also compared between intermediate and premutation ranges in patients. The 5′ UTR of FMR1 gene was amplified using PCR. The numbers of trinucleotide repeats were confirmed by the Sanger sequencing method. The frequency of premutation was higher in POF and DOR patients in comparison with controls, but the difference in the incidence of intermediate alleles was not statistically significant among these groups. The mean level of serum FSH was higher in patients with premutation than patients with intermediate alleles. Based on the current evidence, we concluded that intermediate-sized FMR1 CGG repeat alleles should not be considered as a high-risk factor for POF and DOR.